НЕБЕЗПЕКА ВИНИКНЕННЯ СИБІРСЬКОЇ ЯЗВИ НА НЕКОНТРОЛЬОВАНИХ ТЕРИТОРІЯХ УКРАЇНИ (World Science, 2018)
At the beginning of the XXI century, the distribution of anthrax on the territory of Ukraine did not acquire significant proportions. In most cases, sporadic and group diseases of people were caused by violations of the current veterinary and sanitary legislation. The analysis of statistical data on the registration of anthrax outbreaks among farm animals and the monitoring of dysfunctional points for this disease in Ukraine during the period 1920 - 2017 revealed 24 956 outbreaks of anthrax. Elimination of anthrax only by vaccination is impossible. Given that the pathogens of the disease persist in the land for centuries, additional measures are needed to maintain sanitary order in the burial places. Topicality. Today, the eastern regions of Donetsk and Luhansk are not controlled to ensure a stable epizootic situation on anthrax. Because of this, these regions can be considered as a risk area in the occurrence of the disease. The purpose of the work is to analyze the epizootic situation regarding the anthrax and graves of animals that died from this disease on the territory of Ukraine.